2012
DOI: 10.1590/s1678-86212012000200011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do comportamento de mistura de argamassas através de reometria rotacional

Abstract: A principal etapa de preparação das argamassas consiste na mistura dos materiais sólidos com água. A introdução do líquido conduz a uma série de eventos de aglomeração e desaglomeração no sistema, que, por sua vez, irão resultar em esforços durante essa etapa. Estudos previamente realizados demonstraram a capacidade de mensuração desses esforços através de curvas que relacionam o torque com o tempo em equipamentos como os reômetros. Nessa perspectiva, o objetivo deste trabalho é avaliar como o tempo influencia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
3
0
4
Order By: Relevance
“…According to some researchers, the mixing time is one of the factors that influence the paste homogenization. França et al [36,37] have shown in their research that samples with longer mixing times demonstrate more efficiency, producing more fluid and stable mortars.…”
Section: Determination Of the Mixing Procedures For The Production Of mentioning
confidence: 99%
“…According to some researchers, the mixing time is one of the factors that influence the paste homogenization. França et al [36,37] have shown in their research that samples with longer mixing times demonstrate more efficiency, producing more fluid and stable mortars.…”
Section: Determination Of the Mixing Procedures For The Production Of mentioning
confidence: 99%
“…No entanto, durante o seu preparo nas obras a mistura com a água deve tornar o conjunto homogêneo e contínuo, resultando em um material que flua sem que ocorra segregação das fases [1][2][3]. Acontece que mesmo com o preciso controle na dosagem das matérias-primas, ainda há considerável variabilidade na etapa de mistura, rápida perda da trabalhabilidade, instabilidade do ar, entre outros fatores, que afetam de forma indesejada o desenvolvimento da microestrutura do material aplicado alterando o seu desempenho em uso [4,5]. A primeira etapa da mistura consiste na adsorção da água na superfície das partículas e ocorre a formação dos aglomerados, devido às forças de interação de van de Waals, forças eletrostáticas entre posições de sítios com cargas opostas e forte interação ou ligação envolvendo as moléculas de água ou hidratos [4].…”
Section: Introductionunclassified
“…This point can be determined in the mixing curve as the moment in which the torque levels start to stabilize and the first derivative of the curve tends to zero asymptotically, Figure 1 [2]. Mixing stages can be assessed by torque vs. time curves, while shear cycles performed immediately after mixing provide information regarding the effects of mixing on the rheological behavior of the material, Figure 1 [9]. In Figure 1, each red point marked on the curve indicates a mixing time when the rheological profile of a mortar was evaluated by a shear cycle (accelerating and decelerating with steps at different rotation speeds).…”
Section: Introductionmentioning
confidence: 99%
“…It can be noted that the shorter the mixing time, the larger the difference between acceleration and deceleration curves (hysteresis), indicating that the system was still rheologically unstable because the mixing was incomplete, therefore the mortar needed an additional energyprovided by the shear cycle -to proceed with dispersion and homogenization and, then, achieve a stable state. For longer mixing times, the hysteresis area gets progressively smaller until it zero or almost zero, which indicates that the procedure provided enough energy for an adequate mixing that produced a rheologically stable mortar for the experimental conditions applied [9]. Fibers are generally incorporated into cementitious materials as reinforcements aiming to improve their strength [10], dynamic properties [11,12], resistance to shrinkage cracking and post-failure residual strength [13].…”
Section: Introductionmentioning
confidence: 99%